Chlamydia trachomatis induces the transcriptional activity of host YAP in a Hippo-independent fashion - Caven, Liam T.; Brinkworth, Amanda J.; Carabeo, Rey A. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The obligate intracellular pathogen Chlamydia trachomatis is the causative agent of the most common bacterial sexually transmitted disease worldwide. While the host response to infection by this pathogen has been well characterized, it remains unclear to what extent host gene expression during infection is the product of Chlamydia-directed modulation of host transcription factors. Methods To identify transcription factors potentially modulated by Chlamydia during infection, we infected immortalized endocervical epithelial cells (End1/E6E7) with the anogenital C. trachomatis serovar L2, harvesting polyadenylated RNA for bulk RNA-sequencing. Subsequent experiments elucidating the mechanism of infection-mediated YAP activation assayed YAP target gene expression via qRT-PCR, YAP nuclear translocation via quantitative immunofluorescence, and YAP phosphorylation via Western blotting. Results RNA sequencing of Chlamydia-infected endocervical epithelial cells revealed gene expression consistent with activity of YAP, a transcriptional coactivator implicated in cell proliferation, wound healing, and fibrosis. After confirming induction of YAP target genes during infection, we observed an infection-dependent increase in YAP nuclear translocation sensitive to inhibition of bacterial protein synthesis. While Hippo-mediated phosphoinhibition of YAP at S127 was unaffected by C. trachomatis infection, Hippo-independent phosphorylation at Y357 was increased. Infection did not enhance nuclear translocation of Y357F mutant YAP, illustrating a requirement for phosphorylation at this residue. Pharmacological inhibition of host Src-family kinase activity attenuated YAP Y357 phosphorylation, but not nuclear translocation – which was instead sensitive to inhibition of Abl. Discussion Our results define a transcriptome-altering mechanism of pathogen-directed YAP activation that bypasses canonical inhibition by the Hippo kinase cascade, with a potential link to chlamydial fibrosis and other advanced disease sequelae. Additional study is required to determine the specific role of infection-associated Y357 phosphorylation and Abl activity in chlamydial induction of YAP.